Youth unemployment in the Middle East and North Africa, and the Moroccan case - Uri Dadush (Kiel Institute for the World Economy (IfW), 2019)
Youth unemployment, and unemployment, in the Middle East North Africa (MENA) countries are among the highest in the world. The tendency to generalize, however, is inappropriate as different groups of countries exhibit vastly different labor market outcomes and causes vary. The standard way of thinking about youth unemployment - i.e. demand for labor driven by economic growth and supply driven by demographics - is of limited use in the MENA countries. Other factors, including sectoral composition of growth, the oil and gas endowment, a large pool of underutilized workers, cultural factors, and mismatch appear to play a more important role, as the case study of Morocco illustrates. The prospects for reducing youth unemployment over the next few years are not good. Policy-makers need to pay more attention to the growth of services, especially those that are, and that tend to remain, labor intensive.
Keywords: J23; J48; J61; J71; 330; unemployment; youth bulge; labor demand; labor productivity; Middle East; North Africa; oil states